Inhaled Nitric Oxide Counterbalances ET-1 Dependent Pulmonary Hypertension and Bronchoconstriction in the Pig - M. G. Clement; M. Dimori (Mediators of Inflammation)
In anaesthetized, paralysed, ventilated pigs the ability of inhaled nitric oxide (80 ppm in 02) to reduce the haemodynamic and respiratory effects of endothelin-1 administration (200 pmol/kg, i.v.) was evaluated. The mechanical properties of the respiratory system were evaluated by the rapid airway occlusion technique. The overall respiratory resistance, the interrupter resistance and the additional resistance that reflects the viscoelastic properties of tissues and the inequality of the time constant within the system were also evaluated. The results show that inhaled nitric oxide can act as a selective pulmonary vasodilator and as a bronchodilator to counteract the vasoconstrictor and bronchoconstrictor activity of endothelin-1. In the pig, nitric oxide inhaled at 80 ppm for 6 mitt reduced the changes in respiratory-, interrupter- and additional resistance due to endothelin-1 administration without significantly changing the static and dynamic elastance of the respiratory system.